The Representation of Perpetrators and Victims in Sexual Violence Cases: A Transitivity Analysis of Online News Texts - Zahara, Riantika; Nurlela, Nurlela (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the forms of transitivity in online news texts reporting rape cases by PPDS doctors at Padjadjaran University. The analysis was conducted using the Systemic Functional Linguistics (LSF) approach, especially on the transitivity system which includes elements of process, participants, and circumstance. Data were obtained from three online news texts that were analyzed qualitatively-descriptively. The results of the study indicate that the most dominant process is the existential process, followed by the material and verbal processes, which show an emphasis on the existence of facts, the actions of the perpetrators, and the delivery of information in the text. The most frequently appearing participant element is existential, followed by actor, goal, and sayer and verbiage, which indicates that the text attempts to convey real events as well as statements from related parties. On the other hand, location circumstance is the most prominent element of information, followed by cause and manner circumstance, which underlines the importance of the context of place and background in the news. Overall, the dominance of the existential process and existential participants reflects the character of news texts that emphasize the existence of events objectively and informatively.